Discovering language variation in WhatsApp text interactions - Pérez-Sabater, Carmen (Onomázein, 2015)
This paper reports the process and outcomes of an instructional project to familiarise postgraduate students with research. The study presents MobileVar, a project which complies with the philosophy of the Bologna Declaration regarding students’ acquisition of research competences. By studying language variations in WhatsApp text interactions, participants were encouraged to develop innovative ideas to make a tangible contribution to the field of language and Computer-mediated Communication. Specifically, the research undertaken consisted in analysing new trends in digital communication by observing if the language used in WhatsApp text interactions constituted a new language variety. Authentic messages in Catalan, English and Spanish were studied from the perspective of the strategies of ‘oralised’ written texts addressed by Yus (2011) and other scholars. The debriefing session revealed that age is a determining factor in the pervasive use of non-standard language. From an educational perspective, students’ involvement in a project for research purposes allowed them to develop the strategies needed to carry out research in tertiary education, such as critical thinking, data collection and interpretation, and collaboration with others. Consequently, the relevance of the study is twofold: on the one hand, it increased the competence of postgraduate students in discourse studies research; on the other hand, it connects with Baron’s (2013) proposal regarding the fundamental role of mobile communication in the way written and spoken language is used today, given the current profusion of mobile communication technologies.